Composition Semigroups on Weighted Bergman Spaces Induced by Doubling Weights - Fanglei Wu (Journal of Mathematics)
We prove that composition semigroups are strongly continuous on weighted Bergman spaces with doubling weights. Point spectra and compact resolvent operators of infinitesimal generators of composition semigroups are characterized.